Wpływ polityki cenowej sprzedaży powierzchni reklamowych na przychody wydawców ogólnopolskiej prasy codziennej - Zawadzki, Piotr (The Influence of Advertising Space Sales Pricing Policy on Profits of Nationwide Daily Press Publishers, 2008)
The article presents pricing policy of advertising space sales implemented by nationwide daily press publishers and its influence on their advertising profits. The author presents objectives which can be obtained by the means of price factor, as well as pricing policy components of particular publishers which differentiate the level of prices related to advertising space sales. The article points to advertising profits of particular titles in the period of 2004-2006, and also the share of these titles in an advertising market. The author distinguishes the groups of the biggest publishers and defines the level of CR4 and CR8 indicators presenting the situation of daily press market concentration in Poland. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 181-190